Loss of Acid Sensing Ion Channel-1a and Bicarbonate Administration Attenuate the Severity of Traumatic Brain Injury - Yin, Terry (Public Library of Science, 2013)
Traumatic brain injury (TBI) is a common cause of morbidity and mortality in people of all ages. Following the acute mechanical insult, TBI evolves over the ensuing minutes and days. Understanding the secondary factors that contribute to TBI might suggest therapeutic strategies to reduce the long-term consequences of brain trauma. To assess secondary factors that contribute to TBI, we studied a lateral fluid percussion injury (FPI) model in mice. Following FPI, the brain cortex became acidic, consistent with data from humans following brain trauma. Administering HCO3 − after FPI prevented the acidosis and reduced the extent of neurodegeneration. Because acidosis can activate acid sensing ion channels (ASICs), we also studied ASIC1a−/− mice and found reduced neurodegeneration after FPI. Both HCO3 − administration and loss of ASIC1a also reduced functional deficits caused by FPI. These results suggest that FPI induces cerebral acidosis that activates ASIC channels and contributes to secondary injury in TBI. They also suggest a therapeutic strategy to attenuate the adverse consequences of TBI.